1994
DOI: 10.1093/tropej/40.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Geographical Variations in the Growth Rate of Infants in China Receiving Increasing Dosages of Vitamin D Supplements

Abstract: In theory, sunshine exposure is sufficient to maintain normal vitamin D concentrations for the optimal growth of newborn infants. To determine whether season of birth, latitude (north v. south) and increasing dosages of vitamin D supplements would influence the growth rate for the first 6 months of life, 255 healthy fall-and spring-born infants from two northern and two southern cities in China were randomly assigned to receive either 100, 200, or 400 IU of vitamin D a day. The study showed that season of birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Vitamin D intakes between 340 and 600 IU/day have been reported to have the maximum effect on linear growth of infants [44][45][46]. When Chinese infants were given either 100, 200, or 400 IU of vitamin D/day, none of the infants demonstrated any evidence of rickets [47].…”
Section: Birth To 6 Monthsmentioning
confidence: 99%
“…Vitamin D intakes between 340 and 600 IU/day have been reported to have the maximum effect on linear growth of infants [44][45][46]. When Chinese infants were given either 100, 200, or 400 IU of vitamin D/day, none of the infants demonstrated any evidence of rickets [47].…”
Section: Birth To 6 Monthsmentioning
confidence: 99%
“… ■ Neonates : ► D aily regimens : 400 IU (10 µg) per day for 7 weeks, 408 15 weeks, 304 6 months, 409 , 410 10 months, 411 and 12 months; 329 or 400 IU (10 µg) per day for 3 months in conjunction with maternal supplements of 2000 IU (50 µg) per day 334 or 500–1000 IU (12.5–25 µg) per day for 3 months 412 . Neonatal doses of 100–200 IU (2.5–5 µg) per day for 6 months did not achieve this end point 409 , 410 ► High‐dose regimens : 100 000 IU orally given at 0, 3 and 6 months 413 …”
Section: The Role Of Vitamin Dmentioning
confidence: 99%
“…While supplementation with 100, 200, or 400 IU per day of vitamin D resulted in the prevention of rickets in one study [34], vitamin D intakes between 340 and 600 IU per day have been reported to have the maximum effect on the linear growth of infants [35]. Furthermore, adding to the concept that vitamin D supplementation in children may not only prevent rickets but also contribute to bone growth and the achievement of an optimal peak bone mass, a 2011 meta-analysis of 4 double-blind randomized controlled trials of vitamin D supplementation in the range of 132–2,000 IU vitamin D per day compared to controls (placebo or lower dose) among a total of 639 children suggested a trend toward a small effect on lumbar spine bone mineral density in all treated children (standardized mean difference 0.15; 95% CI –0.01 to 0.31; p = 0.07).…”
Section: Why Is It Important To Avoid Vitamin D Deficiency In Early Cmentioning
confidence: 99%